Modern automated systems of the financial and economic and managerial analysis of economic activity of the entity (Journal of Economic Research & Business Administration, 2017)
In this article value of a financial analysis for the financial managerin modern conditions of development of economy is provided, and alsothe attention on automated systems of the financial and economic andmanagerial analysis of economic activity of the entity is concentrated. Thegreatest attention at the same time is paid to the «Finekanaliz»-2016 Version8.0.165 program.«Finekanaliz» is a professional automated system of the complex financialand economic and managerial analysis of economic activity of anaccounting entity.Main objective of this program – enhancement of a financial analysisof an accounting entity.Financial analysis – «Finekanaliz» represents a packet for automationof the managerial and financial and economic analysis of the organizationsand entities. The program allows to perform periodic monitoring andfinancial analysis of an accounting entity, including also express-analysis,to constitute balance estimations, to model development of a financialsituation, to constitute analytical notes, to develop programs of sanitationand the development strategy of the company.